Agricultural Management Options for Climate Variability and Change: Conservation Tillage - Kip Balkcom; Leah Duzy; Daniel Dourte; Clyde Fraisse (EDIS)
This 4-page fact sheet focuses on the use of conservation tillage in crop production systems as a strategy to minimize the risks associated with climate variability and change and to improve resource-use efficiency. Written by Kip Balkcom, Leah Duzy, Daniel Dourte, and Clyde Fraisse, and published by the UF Department of Agricultural and Biological Engineering, June 2012.